Бухгалтерский учёт в бюджетных организациях - Кондраков Николай Петрович (Проспект, 2008)
Экземпляры: Ч/з (20090610) / Инвентарный номер: 94674 / Цена: 277.00 / Авт.знак: К 64 / ГРНТИ: 06 / ББК: 65.052